THE INFLUENCE OF PERCEPTION OF INTERNAL CONTROL ON FRAUD PREVENTION WITH ANTI-FRAUD AWARENESS AS A MODERATION VARIABLE - Edi Irgi Ardiansyah; Cipto Wardoyo; Endang Sri Andayani (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2024)
The occurrence of fraud can have detrimental effects on the integrity, efficiency, and credibility of public institutions. Therefore, it is crucial to thoroughly examine factors that can help mitigate its impact. This study aims to investigate the role of perceptions about internal control in preventing fraud, with anti-fraud awareness as a moderating variable. The research was conducted in the Probolinggo district of East Java, involving 28 regional government organizations. A representative sample of 150 respondents was collected using cluster sampling. Data was collected through an online questionnaire. The data was analyzed using Structural Equation Modeling-Partial Least Squares Path Modeling (SEM-PLS). The findings of the study indicate a significant positive influence of perceptions about internal control on fraud prevention. However, it was observed that anti-fraud awareness did not enhance the impact of perceptions about internal control on fraud prevention. This research is expected to provide valuable insights for stakeholders involved in fraud prevention, including the regional government organizations in Probolinggo Regency and others.